Increased Artemis levels confer radioresistance to both high and low LET radiation exposures - Sridharan Deepa M; Whalen Mary K; Almendrala Donna; Cucinotta Francis A; Kawahara Misako; Yannone Steven M; Pluth Janice M (Radiation Oncology, 2012)
Abstract Background Artemis has a defined role in V(D)J recombination and has been implicated in the repair of radiation induced double-strand breaks. However the exact function(s) of Artemis in DNA repair and its preferred substrate(s) in vivo remain undefined. Our previous work suggests that Artemis is important for the repair of complex DNA damage like that inflicted by high Linear Energy Transfer (LET) radiation. To establish the contribution of Artemis in repairing DNA damage caused by various radiation qualities, we evaluated the effect of over-expressing Artemis on cell survival, DNA repair, and cell cycle arrest after exposure to high and low LET radiation. Results Our data reveal that Artemis over-expression confers marked radioprotection against both types of radiation, although the radioprotective effect was greater following high LET radiation. Inhibitor studies reveal that the radioprotection imparted by Artemis is primarily dependent on DNA-PK activity, and to a lesser extent on ATM kinase activity. Together, these data suggest a DNA-PK dependent role for Artemis in the repair of complex DNA damage. Conclusions These findings indicate that Artemis levels significantly influence radiation toxicity in human cells and suggest that Artemis inhibition could be a practical target for adjuvant cancer therapies.